An assessment of the effect of extension services on arable farmers' production in Ekiti South west local government area of Ekiti State (2012)
The study investigated the effect of extension services on arable crop farmers' production in Ekiti South West Local Government Area of Ekiti State. Multistage sampling technique was used to select 105 respondents from the list obtained from the state ADR Interview schedule was employed to elicit information from the respondents. Data obtained were subjected, to descriptive and inferential statistics. More than half (55.2%) of the respondents were aged 50 years and above and 57.1%) had no formal education. Majority (83.8%) were married, had a farm size range of 1-2 hectares (80.9%) and had farming experience of not less than 16 years (72.4%). A large percentage of respondents (68.6%) sourced for improved agricultural practices through fellow farmers and 50.5% financed their arable fanning business through cooperative societies' loans. Crops grown by the farmers Include; maize, yam, cassava, okra, vegetable and sweet potato. More than half (52.4%) of the respondents had favourable attitude towards extension services while farmers' production was low among many of them (48.6%). Significant relationship exist between age (r = 0.305). farm size (r = 0.381), years of formal education (r = 0.488), fanning experience (r = 0.643), attitude of fanners towards extension services and their production (r= 0. 196;p<0.05). Farmers had poor but effective extension services on their production. Therefore, arable crop farmers need a dynamic extension service through purposeful contact with extension agents, government should increase the funding, mobility and. motivation of field extension staff to ensure better agricultural production, and invariably. achieve food security in the country.